PENGARUH MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS XI IPS DALAM MATA PELAJARAN AKUNTANSIDI SMA PASUNDAN 7 BANDUNG - Endah, - (2010)
This research is about the influence of studentss learning motivation to students study achievement in XI grader in accountancy lesson in 7 Pasundan senior high school Bandung. The objectives of this research are to learn about description of students learning motivation in social class XI in Pasundan 7 senior high school Bandung, to learn about description of students study achievement and to learn the influence of students learning motivation to students study achievement in social class XI in Pasundan 7 senior high school Bandung. The method of this research is verification survey. This research is sampling research which used in 60 students of 154 populations as its sample. The learning motivation data is collected from questionnaires and students study achievement is collected from the result of final exam in accountancy lesson second semester in social class XI. Illustrations of students learning motivations and also the students study achievement in accountancy lesson are on the medium category. To know how substantial the influence of learning motivation to students study achievement, the writer did determination co-efficient account. Having calculate, we know that the percentage of the influence of students learning motivation to students study achievement in social class XI in accountancy lesson in 7 Pasundan senior high school Bandung as big as 17, 64 % and the rest with 82,36 % is impacted by other factors.